Hubungan Keefektifan Supervisi Akademik Kepala Sekolah dengan Pengembangan Kompetensi Guru di SMA Se-Kecamatan Tidore - Nurdayanti A. Rahman; Novianty Djafri; Besse Marhawati (Universitas Indraprasta PGRI Jakarta, 2022)
The quality of education in schools is also largely determined by the ability of the principal in supervising the implementation of learning carried out by teachers, thus the improvements are made from the results of supervision.This study aims to determine: 1) the effectiveness of the principal’s academic supervision in Senior High Schools in Tidore Sub-district, 2) the development of teacher competence in Senior Highschool in Tidore Sub-district, 3) the relationship between the effectiveness of the principal’s academic supervision and the development of teacher competence in senior High Schools in Tidore Sub-district. This study applies quantitative with a correlational type of research. The data collection techniques consist of questionnaires, observation, and documentation. The results of the study explain that: 1) the effectiveness of academic supervision is in the good category with a percentage of 83%, 2) teacher competency development is in the very good category with a percentage of 90%, 3) there is a positive relationship between the effectiveness of the principal's academic supervision and teacher competency development. at the level of the correlation coefficient of 0,581 or 58%. Therefore, it is necessary to continuously improve the quality of academic supervision and develop self-quality which can be carried out by expanding knowledge and understanding of academic supervision and teacher competency development.